1999
DOI: 10.1093/milmed/164.5.351
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve War Injuries

Abstract: Objective: The purpose of this study is to evaluate peripheral nerve war injuries sustained during the war in southern Croatia and Bosnia and Herzegovina. Patients and Methods: During the war in Croatia, 713 patients (99% male and 1% female) with wounds inflicted by firearms were examined at the Laboratory of Neurophysiology, University Hospital, Split. The patients, soldiers and civilians alike, ranged in age from 6 to 73 years (average, 28 years). All patients with firearm nerve war injuries underwent detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Studies of war victims (soldiers and civilians alike) have shown that peripheral nerve injuries account for approximately 70% to 80% of all trauma (11,12). In the past decade, the focus of neurobiological research has been to develop an ideal nerve growth factor that enhances axonal growth in terms of the rate of advancement and the density of nerve fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of war victims (soldiers and civilians alike) have shown that peripheral nerve injuries account for approximately 70% to 80% of all trauma (11,12). In the past decade, the focus of neurobiological research has been to develop an ideal nerve growth factor that enhances axonal growth in terms of the rate of advancement and the density of nerve fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise incidence of peripheral nerve injury is unknown, it is one of the most common traumatic upper extremity injuries. Studies of war victims (soldiers and civilians alike) have shown that peripheral nerve injuries account for approximately 70% to 80% of all trauma (11,12). In the past decade, the focus of neurobiological research has been to develop an ideal nerve growth factor that enhances axonal growth in terms of the rate of advancement and the density of nerve fibres.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 713 patients (99% male) were reported with peripheral nerve injuries due to war in Croatia and Bosnia and Herzegovina. The majority had single‐nerve lesions with the peroneal (21%) and ulnar (20%) being the most common 36. In U.S. Army casualties of the Persian Gulf Conflict, the most common nerves affected in one report were median (18%), peroneal (16%), ulnar (12%), and radial (11%) 34 ; however, when considering 10‐year outcomes, there was no significant difference in the rate of peripheral neuropathy between deployed and nondeployed Gulf War veterans 37…”
Section: Armed Conflictmentioning
confidence: 99%